PENGARUH GAYA KEPEMIMPINAN DAN POLA KERJA TERHADAP KINERJA PEGAWAI TATA USAHA SMPN DI KECAMATAN KALIDERES KOTA ADMINISTRASI JAKARTA BARAT - Abdul Rosyid (Jurnal Manajemen Pendidikan, 2013)
The objective of this research is to obtain information about the effect of leadership style and job design on administration staff’s job performance of state junior high school. The research was conducted to all of state junior high schools administration staffs in the district of Kalideres, the city of west Jakarta by using a survey method with path analysis applied in testing hypothesis. The research concludes: (1). There is direct effect of leadership style on job performance. (2). There is direct effect of job design on job performance. (3). There is direct effect of leadership style on job performance. Therefore to enhance administration staff’s job performance can be carried out by leadership style and job design.